ChemInform Abstract: Sterically Controlled Iodination of Arenes via Iridium‐Catalyzed C—H Borylation. Issue 21 (2nd May 2013) - Partridge, Benjamin M.; Hartwig, John F.
Abstract The presented new method to prepare (hetero)aryl iodides proceeds via stereocontrolled borylation.